(untitled) (Annals of Medical Research, 2023)
Glioma is one of the most aggressive tumors that develop in the glial cells of the brain. It has subtypes such as astrocytomas, oligodendrogliomas and ependymomas. Gliomas comprise about 30% of all brain tumors and are mostly malignant. Gliomas are classified into four grades and the severity of the disease increases with the grade. Like many cancer types, development of gliomas is under the control of genetic, epigenetic and environmental factors. Epigenetics is the area that examines the expression changes in genes that do not change the structure of DNA, but cause behavioral changes in uncontrolled proliferation, growth, migration, death and many other processes in the cell by affecting the gene. Methylation, acetylation, micro RNAs (miRNAs), histone modifications are among the well-known epigenetic factors. This review aims to describe the most common and well-identified epigenetic changes that can result in glioma formation.